Estudo sobre a cultura de gastos educacionais: os casos de Arapongas e Apucarana (PR) - Chiarelli, Lucinéia (Universidade Federal de São Carlos, 2014)
The main objective of this study focuses on the identification and analysis of expenditure incurred by rural and urban schools of Paraná with a view to calculating the cost-student, through the analysis of public policies implemented in Brazil and financing in the State of Paraná. We decided to make a documentary research, employing a quantitative and qualitative analysis of the brazilian legislation, contained in their constitutions and expressed by a set of policies that govern and regulate the educational field in our country, in particular its financing. The universe involving our research focused on five rural schools from Arapongas twelve urban schools that accept students from rural and twenty-four urban schools serving children and adolescents in the city of Apucarana. We note that the cost-student for the two schools goes far beyond the minimum set by the Brazilian federal government value, as well as specified by the Paraná state government, on average exceeding them up to four times the minimum value. We understand that the use of accounting, its resources and its instruments used both for display and for the analysis of legislation and public policies that regulate, standardize and manage the brazilian educational field can contribute to improving the school realities of individuals living and work in the field.
Study on the culture of educational spending: the cases of Arapongas and Apucarana (PR)
Keywords: Educação; Políticas públicas; Financiamento; Contabilidade; Custos; Qualidade na educação; Education; Public policy; Finance; Accounting; CIENCIAS HUMANAS::EDUCACAO